An Illusion: “A Suzuki Type Coupled Fixed Point Theorem” - Hamed H. Alsulami; Erdal Karapınar; Marwan A. Kutbi; Antonio-Francisco Roldán-López-de-Hierro (Abstract and Applied Analysis)
We admonish to be careful on studying coupled fixed point theorems since most of the reported fixed point results can be easily derived from the existing corresponding theorems in the literature. In particular, we notice that the recent paper [Semwal and Dimri (2014)] has gaps and the announced result is false. The authors claimed that their result generalized the main result in [Ðoric and Lazović (2011)] but, in fact, the contrary case is true. Finally, we present a fixed point theorem for Suzuki type (α, r)-admissible contractions.